2012
DOI: 10.1120/jacmp.v13i6.3769
|View full text |Cite
|
Sign up to set email alerts
|

Noncoplanar intensity‐modulated radiation therapy for young female patients with mediastinal lymphoma

Abstract: The purpose of this study is to apply noncoplanar intensity‐modulated radiation therapy (Nonco_IMRT) to young female patients with mediastinal lymphoma. Nonco_IMRT was evaluated through a planning comparison study with coplanar IMRT (Co_IMRT) and conventional anteroposterior and posteroanterior fields (AP–PA) plans. Co_IMRT was performed with five equally spaced beams starting from a gantry angle of 216°. Nonco_IMRT used two noncoplanar beams in the sagittal plane to replace the Co_IMRT beams that directly irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…(13,14) Dose planning studies have previously suggested that advanced radiotherapy techniques could reduce the dose to the organs at risk (OAR) considered in this work. (15)(16)(17) Brodin et al (18) review models for risks of specific radiation-induced effects in patients with HL, focusing on linear models that rely on mean dose for calculation of risk for cancer induction. Risk estimate comparison studies of IFRT techniques for HL, including volumetric-modulated arc therapy and proton therapy by Maraldo et al, (11,19) also use linear models for calculation of secondary cancer risk.…”
mentioning
confidence: 99%
“…(13,14) Dose planning studies have previously suggested that advanced radiotherapy techniques could reduce the dose to the organs at risk (OAR) considered in this work. (15)(16)(17) Brodin et al (18) review models for risks of specific radiation-induced effects in patients with HL, focusing on linear models that rely on mean dose for calculation of risk for cancer induction. Risk estimate comparison studies of IFRT techniques for HL, including volumetric-modulated arc therapy and proton therapy by Maraldo et al, (11,19) also use linear models for calculation of secondary cancer risk.…”
mentioning
confidence: 99%
“…Xinyuan Chen et al published a study in 2012 compares coplanar to non-coplanar intensity-modulated radiation therapy to young female patients with mediastinal lymphoma the mean dose, V5 and V10 for the breast and lungs are significantly lower in non-coplanar IMRT than in coplanar IMRT (P < 0.05), also the mean dose to the heart significantly reduced in non-coplanar compared to coplanar IMRT [22].…”
Section: Discussionmentioning
confidence: 99%
“…PTV 1 comprises the CTV, including the GTV (i.e., initial tumor mass and lymph node remnant(s)), with an added margin to account for organ movement and set-up variations. PTV 2 consists of the GTV alone, also with a margin to consider organ movement and set-up variations [ 33 ].…”
Section: Design Of Radiation Fieldsmentioning
confidence: 99%